Takhrij and Syarah Hadith of Agrotechnology Selection of Quality Seeds for Quality Harvest Results - Rahmat Gozali; Wahyudin Darmalaksana; Liberty Chaidir (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the selection of quality seeds for quality yields. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is the selection of seeds that aim to contribute to productivity. The conclusion of the research is the takhrij and syarah hadith of the Prophet regarding the selection of quality seeds for quality crops with agrotechnological analysis, the selection of seeds is important to increase productivity.